2021
DOI: 10.22161/ijels.65.32
|View full text |Cite
|
Sign up to set email alerts
|

Science Teachers’ Understanding of Higher Order Thinking Skills

Abstract: For students to become critical, creative, and engage in problem solving, teachers' role is critical. A teacher is required to implement higher order thinking skills activities in the class. The study focused on science teachers' understanding of higher order thinking skills (HOTS) in teaching and learning science. A mixed methods approach was adopted for the study. Data collected from survey questionnaires, classroom observation, interviews and documents analysis were analysed based on descriptive statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…Despite the favourable outlook towards the taxonomy, the findings unveiled that teachers predominantly incorporated lower cognitive levels in their instructional practices, with the application of HOTS largely confined to the construction of assessment items. These findings aligned with the findings of other studies which reported a notable disparity between the teachers' conceptions of the Bloom's Taxonomy and the inclusion of the taxonomy in their instructional practice (Abdullah et al, 2017;Cheda & Utha, 2021;Che Seman et al, 2017;Suhaili, 2014;Wan Yusoff & Che Seman, 2018). As a result, lessons remained at lower-level cognition despite the curriculum requirement that emphasizes on nurturing critical thinking skills.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Despite the favourable outlook towards the taxonomy, the findings unveiled that teachers predominantly incorporated lower cognitive levels in their instructional practices, with the application of HOTS largely confined to the construction of assessment items. These findings aligned with the findings of other studies which reported a notable disparity between the teachers' conceptions of the Bloom's Taxonomy and the inclusion of the taxonomy in their instructional practice (Abdullah et al, 2017;Cheda & Utha, 2021;Che Seman et al, 2017;Suhaili, 2014;Wan Yusoff & Che Seman, 2018). As a result, lessons remained at lower-level cognition despite the curriculum requirement that emphasizes on nurturing critical thinking skills.…”
Section: Discussionsupporting
confidence: 87%
“…Studies exploring teachers' perceptions of higher-order thinking skills (HOTS) and its integration in instructional practice has consistently revealed a reverse relationship. Although teachers have demonstrated positive attitudes toward HOTS and recognized its significance, their teaching methods have predominantly centred on lower-order thinking skills (LOTS) (Cheda & Utha, 2021;Che Seman et al, 2017;Suhaili, 2014;Wan Yusoff & Che Seman, 2018). In a study by Abdullah et al (2017) on teachers' understanding of Bloom's Taxonomy, they observed that while teachers exhibited theoretical familiarity with the taxonomy, they encountered difficulties in distinguishing the differences in the characteristics and applications of LOTS and HOTS.…”
Section: Teachers' Integration Of Hotsmentioning
confidence: 99%
See 2 more Smart Citations